Highly specific blood-brain barrier transmigrating single-domain antibodies selected by an in vivo phage display screening - Aguiar, Sandra I (2021)
© 2021 by the authors. Licensee MDPI, Basel, Switzerland. This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https://creativecommons.org/licenses/by/4.0/).